Rights to Restitution of Victims of Criminal Actions According to Article 7 Section (1) Law Number 13 of 2006 Junction Law 31 of 2014 Concerning the Protection of Witnesses and Victims - Hotma P Sibuea; Indra Lorenly Nainggolan; Jantarda Mauli Hutagalung (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Several research problems that need to be answered are as follows. First, can the granting of victims' restitution rights based on Article 7A paragraph 1 (one) of Law Number 31 of 2014 be carried out by the aims and objectives of the legal principle of "fair legal protection" as regulated in Article 28D paragraph (1) of the 1945 Constitution? Second, is it necessary to reconstruct the arrangement for granting restitution rights in Article 7A paragraph (1) of Law Number 31 of 2014 so that the legal principle of "fair legal protection" as referred to in Article 28D paragraph (1) of the 1945 Constitution can be realized in the Indonesian welfare law state? The research method used is the juridical-normative research method. The conclusions that can be put forward are as follows. First, the granting of restitution rights to victims of criminal acts based on Article 7A paragraph 1 (one) of Law Number 31 of 2014 cannot be carried out by the principle of "fair legal protection" in Article 28D paragraph (1) of the 1945 Constitution because of the legal vacuum regarding the perpetrators. Able to pay restitution. Second, the granting of restitution rights to victims must involve the state when there is a legal vacuum so that the principle of "fair legal protection" based on Article 28D paragraph (1) of the 1945 Constitution can be realized in the Indonesian criminal justice system and the Indonesian welfare law state.